Degradation mechanisms of lithium sulfide (Li2S) composite cathode in carbonate electrolyte and improvement by increasing electrolyte concentration. Issue 6 (25th February 2021) - Mokudai, Hidehisa; Takeuchi, Tomonari; Sakaebe, Hikari; Kobayashi, Hironori; Matsubara, Eiichiro
Abstract : Lithium polysulfides (Li2 S n ) react with carbonate solvents, forming organic polysulfides (R–S n –R) and sulfides (R–S–R); the concentrated electrolyte suppresses these reactions. Abstract : A Li2 S cathode has a high theoretical capacity (1166 mA h g −1 ); however, it is inherently an insulator. To remedy this defect, composite sulfides can be prepared with transition-metal sulfides having better conductivity than Li2 S. Among them, a Li8 FeS5 (Li2 S/FeS = 4/1, mol/mol) cathode theoretically delivers 888 mA h g −1 . This cathode, however, exhibits poor cycling performance in 1.0 M LiPF6 /ethylene carbonate (EC)–dimethyl carbonate (DMC) (EC/DMC = 1/1, v/v) electrolyte; meanwhile, concentrated (3.5 M) electrolyte improves the performance. Herein, we elucidate the degradation mechanisms through analyses of cycled electrolytes and cathode surfaces. We identify organic polysulfides (R–S n –R) (not lithium polysulfides (Li2 S n )) after charging and organic sulfides (R–S–R) after discharging in the 1.0 M electrolyte. Meanwhile, neither are detected in the 3.5 M electrolyte; instead, salt decomposition products (mainly LiF) are detected on the cathode surface. Therefore, electrolyte modifications can further improve the cyclability of sulfur-based secondary batteries including lithium–sulfur battery.